Etomidate-induced hypokalemia in electronic cigarette users: two case reports and literature review - Wu, Wenchang; Xia, Can; Gan, Lulu; Liao, Shibo; Yan, Yimin (Frontiers in Endocrinology, 2024)
Hypokalemia is a common clinical condition that can lead to muscle weakness, difficulty breathing, malignant arrhythmias, and even death. This report describes two cases of severe hypokalemia resulting from the use of electronic cigarettes containing etomidate, both accompanied by varying degrees of adrenal hyperplasia.In both cases, the patients were admitted to the hospital with lower limb weakness and difficulty walking. Relevant examinations revealed low blood potassium, low cortisol, high adrenocorticotropic hormone, low renin, and low aldosterone levels in the patients, with Case 2 also having significant hypertension. In both cases, adrenal CT scans showed thickening of the adrenal glands. After the delivery of potassium supplementation in both cases, blood potassium levels gradually returned to normal and muscle strength gradually improved. The case reports are followed by a review of the literature on etomidate and its related mechanisms of action with discussion of its association with hypokalemia.